The Development of Fatwas Based on Local Wisdom to the National Level: A Case Study of Panaik Money Fatwa - Syatar, Abdul; Bakry, Muammar; Bedong, M. Ali Rusdi; Ahmad, Ahmad; Pallawagau, Baso (El-Mashlahah, 2023)
The fatwa of the Indonesian Ulema Council of South Sulawesi Province regarding panaik money is debated and considered cynical by some people who feel disturbed. The cultural shift in